Transforming Tawhid Learning with Augmented Reality: A Case Study in Madrasah Ibtidaiyah - Iqbal, Muhammad; ., Silahuddin (Universitas Negeri Medan, 2024)
The concept of Tawhid is the core of Islamic teachings that every Muslim must understand profoundly, especially from an early age. However, teaching Tawhid often faces significant challenges because of its abstract nature, which makes it difficult for students at the Madrasah Ibtidaiyah level to comprehend. This research aims to overcome this problem by utilizing Augmented Reality (AR) technology as an interactive and engaging learning aid. This research employed a case study method at Madrasah Ibtidaiyah to design, develop, and test the effectiveness of AR-based Tawhid learning materials. The initial stage of the research involved a needs analysis through surveys and interviews with teachers and students to identify challenges in teaching Tawhid. Based on the results of this analysis, AR-based Tawhid learning materials were developed and implemented. The effectiveness testing was carried out by comparing students' understanding before and after using AR through pre-tests and post-tests. Additionally, feedback from teachers and students was also collected to evaluate the user experience and the applicability of this technology in the context of daily learning. The results showed that the use of AR technology significantly improved students' understanding of the Tawhid concept. Students became more interested and motivated to learn, and the abstract concepts of Tawhid could be understood more concretely and visually. Positive feedback from teachers and students also affirmed that AR is an effective and enjoyable tool in religious education. Thus, this research concludes that AR technology has great potential to be applied in Islamic education, particularly in teaching abstract concepts such as Tawhid. The use of AR not only enhances students' understanding but also makes the teaching and learning process more interactive and engaging.